Shear behaviour of reinforced concrete beams under impact loads by the Lumped Damage framework - Mateus Cardoso Oliveira; Daniel Victor da Cunha Teles; David Leonardo Nascimento de Figueiredo Amorim (Fracture and Structural Integrity)
Impact loadings such as vehicle collisions or falling rocks on a structure could lead it to collapse and, eventually, to fatal victims. Among possible alternatives to analyse this issue, Lumped Damage Mechanics is an interesting option due to its formulation and easiness for practical application. Therefore, this paper presents a simplified Lumped Damage model to evaluate reinforced concrete structures under impact loads with shear failure mode. In the proposed approach, the damage variable is considered as an output parameter. Such damage variable takes values between zero and one, which quantifies the concrete cracking due to impact loading. The proposed formulation was applied in experiments of reinforced concrete beams under impact loads that presents shear collapse. The obtained results showed good accuracy between the proposed model and the actual structural behaviour. Moreover, a possible flowchart for practical applications is also presented. Since the model parameters are easily associated to inelastic phenomena, the proposed formulation might become accessible to engineers in practice.